What You Believe Can Affect How You Feel: Anger Among Caregivers of Elderly People With Dementia - Wang, Haoran; Cui, Hongmei; Wang, Meng; Yang, Chunyan (Frontiers in Psychiatry, 2021)
Background & Purpose Anger has been recognized as one commonly experienced mood among caregivers of elderly people with dementia. While several CBT-based intervening methods have been developed, few researches have examined systematically the associations between dementia-related cognitions and caregiving anger. Currently, we focused on three representative and well-studied cognitive constructs, Person-Centered Attitude (PCA), Dementia Representation (DR) and empathy, exploring how they related to caregiving anger. Methods & Results Total 327 caregivers (239 female) participated in the study and finished online questionnaires. Multi-variable regression analyzes showed that PCA (β PCA= -.30**), empathy (β empathy= -.11**) could negatively predict caregiving anger. However, all DR dimensions have no influence on caregiving anger except Coherence (β Coherence= -.27) in the current study. Conclusion Generally, lower caregiving anger was associated with: (1) being more empathic; (2) holding a Person-Centered Attitude; (3) having a comprehensive understanding of dementia. The results of this study provide detailed suggestions to the development of anger-managing programs for caregivers of people with dementia.